2022
DOI: 10.1039/d2ra04790j
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism and principle of doping: realizing of silver incorporation in CdS thin filmviadoping concentration effect

Abstract: A high-quality buffer layer serves as one of the most significant issues that influences the efficiency of solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Figure 7 b illustrates the slight displacement of CdS-doped Ag from their pre-doping positions, at 2θ = 27.84°, oriented along the (002) (JCPDS-00-041-1049). Changes in peak position and FWHM suggest that Ag doping affects the microstructure, crystal quality, and lattice parameters 35 . Figure 7 c, showed that the strong peak a little bit shifting positioned at 2θ = 26.94°, is oriented along with the (111) and (002), directions and is in good agreement with the (JCPDS-01-075-0581) and (JCPDS-01-080-0006), suggesting both cubic and hexagonal form.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 b illustrates the slight displacement of CdS-doped Ag from their pre-doping positions, at 2θ = 27.84°, oriented along the (002) (JCPDS-00-041-1049). Changes in peak position and FWHM suggest that Ag doping affects the microstructure, crystal quality, and lattice parameters 35 . Figure 7 c, showed that the strong peak a little bit shifting positioned at 2θ = 26.94°, is oriented along with the (111) and (002), directions and is in good agreement with the (JCPDS-01-075-0581) and (JCPDS-01-080-0006), suggesting both cubic and hexagonal form.…”
Section: Resultsmentioning
confidence: 99%